Prevalence of Obesity Among Adults in Sinjar District, Iraq: Its Association with Common Chronic Diseases and Some Inflammatory Biomarkers - Alsafar, Ashraf; Sehree, Mohanad (Libyan Journal of Medical and Applied Sciences, 2026)
Obesity is defined as excessive accumulation of body fat resulting from an imbalance between calories consumed and calories burned. This study aimed to determine the prevalence of obesity and overweight among adults in Sinjar District, Iraq, compared to other Iraqi cities. It also sought to confirm the relationship between the accumulation of adipose tissue, elevated levels of inflammatry markers, and the development of certain chronic diseases. It is worth noting that the Yazidi community in Sinjar differs ethnically, culturally, and religiously from the Arab majority in the country. This cross-sectional study included 240 adults aged 18–80 years, randomly selected between February and April 2025. Serum glucose, lipids, interleukin-6, and C-reactive protein levels were measured to assess biomarkers associated with obesity. The results showed that, compared to other Iraqi cities, Sinjar recorded lower levels of obesity, but its overweight figures remained consistent with the general averages observed in previous research. A strong association was observed between body mass index (BMI) and the development of diabetes and cardiovascular disease, with significant increases (P < 0.05) in glucose, low-density lipoprotein (LDL), Triglyceride (TG), and inflammatory markers among overweight and obese individuals. This study concluded that the ethnic and cultural distinctiveness of the Yazidi community in the Sinjar district may have contributed to recording relatively low obesity rates compared to other Iraqi cities. The study also confirms a close relationship between increased fat mass and elevated inflammatory markers and metabolic disorders, reinforcing the role of obesity as a major risk factor for the spread of chronic diseases in the region.